Identification and characterisation of tail components modulating host range of Clostridium difficile phages - Steczynska, Joanna (2023)
Clostridium difficile is an anaerobic, spore-forming, pathogenic bacterium that is the leading cause of antibiotic-associated diarrhoea. The infection is treatable with a few antibiotics, however, due to the ever-increasing rates of antibiotic resistance and risk of relapse, novel therapies are in demand. This study focused on advancing the path towards using phages as therapeutic agents against the infection. Genes which are potentially responsible for encoding the receptor binding protein (RBP) found on the phage were investigated. The RBP, encoding the tail fibre, is responsible for garnering the binding specificity of phages. Currently, antibiotics used against the infection are broad spectrum which contributes to the problem, whereas, the phages infecting C. difficile present the opposite problem of having a too narrow host range to target all clinically relevant strains with a single phage. This study generated RBP mutants using a CRISPR/Cas9 system in phages ΦCD1801, ΦCD2301, and ΦCD2315 infecting different PCR ribotypes, to confirm the putative RBP gene as responsible for binding specificity. Mutant phages were assayed for their binding ability, with ΦCD1801 imaged under TEM to examine the resulting virion. Further, accessory and structural genes surrounding the RBP were studied in the same manner, through deletion and exchange mutants, swapping various components within the tail module between ΦCD1801 and ΦCD2301 to achieve a host range change. A resulting mutant phage, Ex11, based on ΦCD2301, was able to infect CD1801, the propagating host of ΦCD1801 when carrying its RBP supported by an accessory gene. The tail module was also characterised, establishing the essential and specificity-conferring genes in Myoviridae. In addition, novel phages ΦL12S, ΦL12W and ΦL14 were isolated from environmental samples and characterised for their particle morphology, genome content and host range. No identifiable integrase gene was found in ΦL14, and the phage was unable to form lysogens in vitro, making it the first potentially lytic phage of C. difficile to be reported. These findings address the two major problems facing therapeutic application of phages against C. difficile and will be instrumental in broadening the host range and overcoming lysogeny.